Implantable Pulse Generators for Deep Brain Stimulation: Challenges, Complications, and Strategies for Practicality and Longevity - Sarica, Can; Iorio-Morin, Christian; Aguirre-Padilla, David H.; Najjar, Ahmed; Paff, Michelle; Fomenko, Anton; Yamamoto, Kazuaki; Zemmar, Ajmal; Lipsman, Nir; Ibrahim, George M.; Hamani, Clement; Hodaie, Mojgan; et al. (Frontiers in Human Neuroscience, 2021)
Deep brain stimulation (DBS) represents an important treatment modality for movement disorders and other circuitopathies. Despite their miniaturization and increasing sophistication, DBS systems share a common set of components of which the implantable pulse generation (IPG) is the core power supply and programmable element. Here we provide an overview of key hardware and software specifications of commercially available IPG systems such as rechargeability, MRI compatibility, electrode configuration, pulse delivery, IPG case architecture, and local field potential sensing. We present evidence-based approaches to mitigate hardware complications, of which infection represents the most important factor. Strategies correlating positively with decreased complications include antibiotic impregnation and co-administration and other surgical considerations during IPG implantation such as the use of tack-up sutures and smaller profile devices. Strategies aimed at maximizing battery longevity include patient-related elements such as reliability of IPG recharging or consistency of nightly device shutoff, and device-specific such as parameter delivery, choice of lead configuration, implantation location and careful selection of electrode materials to minimize impedance mismatch. Finally, experimental DBS systems such as ultrasound, magnetoelectric nanoparticles and near-infrared that use extracorporeal powered neuromodulation strategies are described as potential future directions for minimal invasive treatment.